Reflections of a Research Team on Using Creative Facilitation for the First Time: Illuminating the Lived Experience of the School Holidays for Children and Families Living in Poverty Across England - Florence Darling; Laura Mazzoli Smith; Mary Robson; Laura Tinner; Marie Murphy; Miranda Pallan; Jessica Tanner; Lorna Hatch; Russell Jago; Carolyn Summerbell (International Journal of Qualitative Methods)
Understanding the lived experience of communities of people who are most affected by health inequalities has become a key focus of public health research. In this context, researchers are increasingly using creative (or arts-based) methods, but there is limited understanding about how best to facilitate these methods to qualitative inquiry that illuminate lived experience and the values that underpin this approach. This paper reports the reflections of researchers who used creative facilitation (a set of tools) in workshops, as part of a research project, which explored how children and families across England, living in poverty, experience the school holidays, including leisure during school holidays. Two professional creative facilitators delivered a two-day training course for the research team in advance of the workshops. Following the workshops, the researchers and facilitators took part in focus groups and a survey which captured their reflections on using creative facilitation. Creative facilitation was deemed to generate new insights on school holiday experiences, providing a greater depth of nuance and understanding and more meaningful and person-centred data. Three key aspects of creative facilitation were identified. First, creating a welcoming research environment, underpinned by positive relationships, where there is trust and an authentic focus on participant choice, comfort, value, empowerment, inclusion and diversity. Second, promoting unconditional positive regard and an ethics of care; the tension between adhering to ethics procedures at the start of the workshop when trying to create a welcoming environment was highlighted as a significant challenge. Third, being adaptive and responsive during the session; the level of flexibility needed during the workshops was challenging, and sometimes uncomfortable, for researchers. Researchers reflected that further experience, ongoing support, and rethinking the ‘scaffolding’ of their approach, would develop their capability in the longer term. We offer suggestions for future activity around creative facilitation for public health research.